Contribución al estudio de los peces Cheirodontinae (Familia Characidae) de Costa Rica y Panamá. Géneros Compsura y Pseudocheirodon - López S., Myrna I. (1972)
The present paper defines the taxonomic position of Compsura gorgonae. The genus Pseudocheirodon is maintained tentatively distinct from Cheirodon. Compsura gorgonae is distinguished from Pseudocheirodon affinis by the presence of spines on the anal fin of males, fewer maxillary teeth and longer maxillary bone. A key is pravided to distinguish the genera Compsura, Cheirodon, Odontostilbe and Pseudocheirodon. Over 2,800 specimens from 54 Panamanian and Costa Rican collections were utilized. The number of lateral line pores of C. gorgonae increases in a westward direction and this may be related to the shorter rivers of steeper gradient and more turbid waters in the rainy season in western Panamá. The number of lateral line pares of P. affinis, also quite variable (7-3 3), showed a random rather than clinal varíation. Both the above species, when sympatric, exhibit nearly the same average number of lateral line pares, which suggests an adaptation to the same enviranmental factors. The length of the maxillary bone of C. gorgondo decreased from east to west, whereas in P. affinis the situation was reversed. No hypothesis could be offered for this latter relationship.